P116 Neatstik® – a novel point of care test for the measurement of active neutrophil elastase in patients with respiratory disease. (15th November 2017) - McCafferty, DF; Moffitt, KL; Tong, W; Ferguson, TEG; Robb, C; Martin, SL; Walker, B
Abstract : Introduction and Objectives: Sputum levels of active neutrophil elastase (NE) are frequently elevated in respiratory diseases, such as bronchiectasis, chronic obstructive pulmonary disease (COPD), and cystic fibrosis (CF). Increased NE levels have been demonstrated to inversely correlate with pulmonary function, and risk of exacerbations. Active NE is also recognised as a biomarker of subclinical infection; however, no tools presently exist for its routine monitoring at home or in the clinic. Translation of the ProAxsis NE Activity Based Immunoassay (ABI) to a Point of Care (PoC) device, would facilitate routine monitoring of those patients at highest risk of upcoming exacerbations; enabling pre-emptive medical intervention, and mitigating the patient's risk of developing serious complications. Methods: Active NE levels in sputum samples (n=10) were determined using the NE ABI (ProAxsis Ltd, Belfast), in accordance with manufacturer's instructions; followed by assessment using the NEATstik PoC test (threshold 10 µg/ml in sputum). For measurement of NE using NEATstik, sputum was diluted x10, gently rotated for 1 min, an aliquot (70 µl) was then transferred onto the test sample port of the device and allowed to develop for 10 min, after which the signal intensity at the test-line was visually graded (0–10). Results: NE ABI analysis of sputum revealed that 7 out of 10 samples under investigation contained active NE at levels above the NEATstik test threshold. All 7 samples were found to produce a strong positive test line on the PoC device. Moreover, no test line was visible for the remaining samples with active NE concentrations below 10 µg/ml. Conclusion: Availability of NEATstik, the first highly sensitive and specific PoC test for the rapid detection of active NE in complex clinical samples, should enable the proactive management of multiple chronic respiratory diseases. It has the potential to assist in the identification of patients at highest risk of imminent exacerbations, and thus allow closer monitoring by their clinical team and/or pre-emptive treatment to avoid/minimise the impact of such exacerbations. Additionally, for those presenting with an ongoing exacerbation, the test facilitates patient stratification, with those most likely to respond to antibiotic therapy identified and their response to treatment assessed.